ANALISIS KINERJA PEGAWAI PADA BIDANG SUMBER DAYA AIR DINAS PEKERJAAN UMUM KABUPATEN DONGGALA - Lage, Alfianus H. (Katalogis, 2017)
The problem in this researchis is how the performance of employees of water resources public works Donggala?. As for the purpose ofÂ  this research is to analysze the performance of employess or water resource donggala public works agencies. The typeof research is desearch is descriptive qualitative research. This research conductaed dilingkungan public work where the informants ini the research sampling set by purposive sampling where the informants selected based on the intent of study. Techniques of collecting data through observation,interviews, and documents. The results showed that the performance of employees in the midwife water resources public works Donggala categorized quite good, for 3 (three), because of the three (3) aspects of performance proposed by Hasibuan only two that are already running are already well underway ie on the business aspects and aspects of opportunity in work which is in force in the field of water resources, and aspects of employee skill in a work that has not lasted up or quite good.